Factors influence novice programmers toward test first approach - Yahya, Norzariyah; Maidin, Siti Sarah; Soomro, Arjumand Bano (World Academy of Research in Science and Engineering, 2019)
Test First is one of the Agile development approaches. In practice, Test First needs a developer to design test cases followed by the development of actual codes. The previous study on Test First has been covering the quality of the codes, either internal quality of codes, external quality of codes, or productivity of codes. Also, research on the behavior of the developers toward Test First based on the developers experiences implementing the Test First approach. This research is looking into the behavior of developers, which focus on finding the factors that influence novice programmers’ to execute Test First by using the Theory of Planned Behavior as the theoretical framework. The Theory of Planned Behavior framework is used to identify the factors that contribute to the Intention of novice programmers’ to implement Test First. The factors were identified quantitatively using a set of questionnaire. The results indicated that Behavioral Beliefs, Attitude towards Behavior, Normative Beliefs, and Subjective Norms are the factors that influenced novice programmers to implement Test First. © 2019, World Academy of Research in Science and Engineering. All rights reserved.